Soporte social, familiar y autoconcepto: relación entre los constructos - Baptista, Makilim Nunes; Rigotto, Daiene Marcela; Cardoso, Hugo Ferrari [UNESP]; Rueda, Fabián Javier Marín (My University, 2012)
This study aimed at verifying the associations between social support, family support and self-concept in a group of men and women. In the male group there were negative correlations between family support and the factors negligence, aggression and indifference of the instrument of self-concept. In the female group, the total family support was positively correlated with sensuality and accountability, and negatively with uncertainty, and these three measures of the instrument of self-concept. The observed relationships between family support and social support were positive, for both men and women.

El objetivo del estudio fue verificar las asociaciones entre el soporte social, el soporte familiar y el autoconcepto en un grupo de hombres y mujeres. En el caso de los hombres hubo correlaciones negativas entre el soporte familiar y los factores negligencia, agresividad e indiferencia del instrumento de autoconcepto. En el grupo de mujeres el soporte familiar total fue correlacionado positivamente con sensualidad y responsabilidad, y negativamente con inseguridad, siendo las tres medidas del instrumento de autoconcepto. Al considerar las relaciones entre el soporte familiar y el soporte social, todas fueron positivas, tanto en los hombres como en las mujeres.
Social support, family and self-concept: constructs relations
Keywords: Family; Self-concept; Social support; Family support; Autoconcepto; Familia; Soporte social; Soporte familiar